2018
DOI: 10.1016/j.jcmgh.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Receptor-Targeted Polyplex Nanoparticle Inhibits Growth and Metastasis of Pancreatic Cancer

Abstract: Background & AimsPancreatic ductal adenocarcinoma (PDAC) remains the most aggressive malignancy with the lowest 5-year survival rate of all cancers in part owing to the lack of tumor-specific therapy and the rapid metastatic nature of this cancer. The gastrointestinal peptide gastrin is a trophic peptide that stimulates growth of PDAC in an autocrine fashion by interaction with the cholecystokinin receptor that is overexpressed in this malignancy.MethodsWe developed a therapeutic novel polyplex nanoparticle (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Watson and colleagues (60) previously showed that passive immunization with rabbit PAS-induced antibodies decreased the number and size of metastases of colorectal cancer in an immune deficient mouse. We formerly demonstrated that a nanoparticle delivering siRNA to gastrin also completely prevented metastases in athymic nude mice bearing human pancreatic tumors (8). Thus strategies that decrease circulating or endogenous tumor production of gastrin have been shown to inhibit metastases from gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Watson and colleagues (60) previously showed that passive immunization with rabbit PAS-induced antibodies decreased the number and size of metastases of colorectal cancer in an immune deficient mouse. We formerly demonstrated that a nanoparticle delivering siRNA to gastrin also completely prevented metastases in athymic nude mice bearing human pancreatic tumors (8). Thus strategies that decrease circulating or endogenous tumor production of gastrin have been shown to inhibit metastases from gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different gastrin‐mediated delivery systems have been designed to target gastrin mRNA in pancreatic cancer cells. In one of these studies, gastrin‐10‐polyethylene glycol‐poly( l ‐lysine) (Ga‐10‐[PEG]5k‐PLL27) has been developed by Burks et al (2018) to deliver gastrin siRNA into the pancreatic tumor cells. The Ga‐conjugated carrier revealed greater gene silencing of gastrin in PANC‐1 cells than unmodified ones.…”
Section: Nanoparticles‐based Delivery Systems For Pancreatic Cancer Sirna Therapymentioning
confidence: 99%
“…Therefore, to target gastrin mRNA in pancreatic cancer cells, some researchers use gastrin-mediated delivery. In one of these studies, gastrinpolyethylene glycol-poly(L-lysine) (Ga-[PEG]5k-PLL27) has been designed by Burks and his co-workers (Burks et al, 2018) to deliver gastrin siRNA into the pancreatic tumor cells. The Ga-conjugated carrier revealed greater gene silencing of gastrin in PANC-1 cells than unmodified ones.…”
Section: Gastrinmentioning
confidence: 99%